Some aspects of the ecology and biology of two estuarine grapsoid crabs - Warren, Stephanie Judith (Rhodes University, Faculty of Science, Department of Zoology, 1964)
Extracted from Summary, p. 172. The semi-terrestrial grapsoid crabs Cyclograpsus punctatus and Sesarma catenata have been studied in two ways. Part I of this thesis gives an account of their distribution in the Kowie River estuary in relation to certain environmental factors. Part II deals with further aspects of their biology as well as the ecological relationship between the two species.
Keywords: Crabs -- South Africa